Pengaruh Minat Belajar dan Motivasi Belajar terhadap Prestasi Belajar Mahasiswa Program Studi Matematika pada Mata Kuliah Statistika Deskriptif - Rani Kurnia Putri; Darvi Mailisa Putri; Lilis Harianti Hasibuan (JOSTECH Journal of Science and Technology, 2023)
This study aims to describe the effect of interest in learning and learning motivation on student achievement in the mathematics study program at the Imam Bonjol State Islamic University, Padang. The type of research used is quantitative. The sample used in this study was 74 students using simple random sampling. This study used instruments on the scale of interest in learning and learning motivation as well as documentation of student achievement in the mathematics study program. Data analysis used in this research is descriptive statistical analysis and multiple regression analysis. The results of this study indicate that interest in learning and learning motivation affect student achievement in mathematics study programs in descriptive statistics courses obtained by the multiple linear regression equation The variables of learning motivation and interest in learning have a contribution of 0.485 or around 48.5% while the rest are influenced by other factors.